The syphilis care cascade: tracking the course of care after screening positive among men and transgender women who have sex with men in Lima, Peru. Issue 9 (18th September 2015) - Tang, Eric C; Segura, Eddy R; Clark, Jesse L; Sanchez, Jorge; Lama, Javier R
Abstract : Objectives: Syphilis is endemic among men who have sex with men (MSM) and transgender women in Latin America. The objective of this study was to assess if those who screen positive for syphilis are receiving appropriate care and treatment. Methods: We use data from the 2011 Peruvian National HIV Sentinel Surveillance to describe the syphilis care cascade among high-risk MSM and transgender women. Medical records from participants who had a positive syphilis screening test at two of the enrolment sites in Lima were reviewed to determine their subsequent course of care. Results: We identified a cohort of 314 syphilis seropositive participants (median age: 30, 33.7% self-identified as transgender). Only 284/314 (90.4%) participants saw a physician for evaluation within 28 days of their positive test. Of these, 72/284 (25.4%) were asked to return for confirmatory results before deciding whether or not to start treatment; however, 45/72 (62.5%) of these participants did not follow up within 28 days. Of the people prescribed three weekly doses of penicillin, 34/63 (54%) received all three doses on time. Conclusions: Many MSM and transgender women with a positive syphilis screening test are lost at various steps along the syphilis care cascade and may have persistent infection. Interventions in this population are needed to increase testing, link seropositive patients into care and ensure that they receive appropriate and timely treatment.